Assessing Health-Related Quality of Life in the Greek Home Health Care Setting: Comparing Cancer Patients' and Nurses' Assessment. (August 2015) - Adamakidou, Theodoula; Galanis, Petros; Kallergis, George; Katostaras, Theofanis; Patiraki, Elisabeth; Kalokerinou, Athena
The study's aim was to evaluate the agreement between patients' and nurses' ratings of patients' health-related quality of life (HRQoL) and to identify factors that affect their level of agreement. A total of 150 home health care cancer patients from Greece and all nurses ( N = 5) who worked in the home health care units completed the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire–Core 30 (EORTC QLQ-C30). Intraclass correlation coefficients varied between .45 and .87, indicating a moderate to excellent agreement. Median absolute difference on QLQ-C30 scores ranged from 0.00 to 16.66 points on the 0 to 100 scale. Cohen's d varied between −0.15 and 0.59. Nurses' higher educational level was associated with greater agreement ( p = .05). Nurses assessed lower the QoL of patients who were completely disabled than the patients themselves did ( p = .005). Our findings suggest that Greek home health care nurses estimate patients' QoL in a reliable and valid way.